Model Kriteria Bahan Bacaan Literasi untuk Siswa SD Berdasarkan Perkembangan Moral Berbasis Cerita Rakyat Banten - Ulinnuha Ulinnuha; Nadofah Nadofah; Aditya Rachman; Rini Sulastri; Diofani Diofani (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
The moral crisis continues to be a concern for Indonesian society today. Therefore, reading literacy in elementary schools is an appropriate strategy that is not only oriented towards the ability to understand texts but also plays an important role in the formation of students' morals and character. The selection of literacy reading materials needs to be adjusted to the stage of moral development of students so that the values contained in the reading can be understood and internalized optimally. This article aims to examine the criteria for literacy reading materials based on the moral development of elementary school students based on Banten Province folklore. The method used is a literature study by analyzing the theory of children's moral development, criteria for selecting literacy reading materials, and moral values contained in Banten folklore. The results of the study indicate that Banten Province folklore has great potential as literacy reading materials that are appropriate to the moral development of  elementary school students because they contain values of honesty, responsibility, hard work, courage, leadership, empathy, social concern, and religiosity. Thus, Banten folklore is relevant to be used as literacy reading materials that support character learning in elementary schools.